2017
DOI: 10.1371/journal.pone.0170999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MiR-21-5p as a Functional Regulator of Mesothelin Expression Using MicroRNA Capture Affinity Coupled with Next Generation Sequencing

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that regulate mRNA expression mainly by silencing target transcripts via binding to miRNA recognition elements (MREs) in the 3’untranslated region (3’UTR). The identification of bona fide targets is challenging for researchers working on the functional aspect of miRNAs. Recently, we developed a method (miR-CATCH) based on biotinylated DNA antisense oligonucleotides that capture the mRNA of interest and facilitates the characterisation of miRNAs::mRNA interactions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…miRNA dysregulation has also been found in MPM [ 9 ], possibly involved in carcinogenesis [ 10 ]. In particular, several papers reported miR-21 over-expression in MPM [ 11 13 ] and we recently demonstrated its reliability as MPM marker [ 14 ]. However, miRNA quantification is not easily available in all laboratories and it would be preferable to use the more common immuno-cyto-chemistry.…”
Section: Introductionmentioning
confidence: 91%
“…miRNA dysregulation has also been found in MPM [ 9 ], possibly involved in carcinogenesis [ 10 ]. In particular, several papers reported miR-21 over-expression in MPM [ 11 13 ] and we recently demonstrated its reliability as MPM marker [ 14 ]. However, miRNA quantification is not easily available in all laboratories and it would be preferable to use the more common immuno-cyto-chemistry.…”
Section: Introductionmentioning
confidence: 91%
“…We demonstrated the effectiveness of a miR‐CATCH method, used to identify biologically active miRNA regulators of an experimentally proven engineering gene, XIAP, which could subsequently be used for genetic engineering without burdening the cells translational machinery. This method has previously been exploited to identify valid miRNA regulators of various genes such as miR‐21‐5p for mesothelin (MSLN) and miR‐659‐3p for progranulin (GRN) but has never been performed in a CHO cell context.…”
Section: Discussionmentioning
confidence: 99%
“…Using a mimic to restore expression levels revealed miR-29c-5p to have modest tumor (8,9) miR-16-5p ↓ ↓ None √ √ * Tumor suppressor functions; downregulates CCND1, BCL2, and PD-L1 TS (8,9) miR-17-5p ↓ ↓ High Exp = SS √ -Inhibits migration; targets KCNMA1 TS (10) miR-18a-5p ↑ N.D. High Exp = SS √ -Antimir causes modest growth inhibition; targets PIAS3 OncomiR (11) miR-21-5p N.D. ↑ High Exp = SS √ -Mimic causes modest growth inhibition; targets mesothelin TS? (12)(13)(14) miR-24-3p ↑ ↑ N.D. √ ( √ ) Promotes migration and tumor growth in mice; targets CGN Oncomir (15) miR-29c-5p ↓ N.D. High Exp = LS √ -Mimic inhibits growth and migration; targets DNMT1/3A TS (16) miR-31-5p ↓ ↓ High Exp = SS √ -Mimic inhibits growth and migration; targets PPP6C; role in drug resistance TS? (17)(18)(19) miR-34a-5p ↓ ↓ N.D. √ √ i Lost in genetically modified mouse model; targets c-Met TS (20)(21)(22)(23) miR-34b-3p ↓ ↓ N.D. √ √ Inhibits MPM growth, enhance radiosensitivity; inhibitors promote mesothelial proliferation TS (21,22,(24)(25)(26) suppressor activity in two MPM cell lines in vitro, by inhibition of proliferation and migration/invasion.…”
Section: Modulating Microrna Levels In Mpm Tumor Suppressor Mirnas-eamentioning
confidence: 99%
“…In light of these observations, it is surprising that the only study to date to assess miR-21-5p activity in MPM suggests that it has modest tumor suppressor function. In a study designed to identify regulators of the MPM marker mesothelin (MSLN), both miR-21-5p and miR-100-5p were found to interact with the MSLN 3'UTR (14). Further experimentation revealed that a miR-21-5p mimic led to modest but significant inhibition of proliferation in two MPM cell lines, with a more pronounced reduction in colony forming ability.…”
Section: Mirnas With Unexpected Activity In Mpmmentioning
confidence: 99%